Impact of statins as immune-modulatory agents on inflammatory markers in adults with chronic diseases: A systematic review and meta-analysis - Solima Sabeel; Bongani Motaung; Kim A. Nguyen; Mumin Ozturk; Sandra L. Mukasa; Karen Wolmarans; Dirk J. Blom; Karen Sliwa; Emmanuel Nepolo; Gunar Günther; Robert J. Wilkinson; Claudia Schacht; et al. (PLoS ONE, 2025)
While numerous studies have extensively documented the pleiotropic effects of statins, including their capacity to reduce inflammation, there is a lack of research estimating the anti-inflammatory effectiveness of statins among individuals with chronic diseases. This meta-analysis evaluates the effect of statin therapy on inflammatory markers and the lipid profile in patients with chronic diseases by analysing evidence from randomized controlled trials (RCTs). We conducted a systematic review and searched articles published between 1st January 1999 and 31st December 2023 in databases including PubMed, Web of Science, Scopus, and Cochrane. The meta-analysis was performed using random effects models and inverse variance. Effect measures were mean differences (MD) and 95% confidence intervals (CI). Collectively, statins significantly reduced IL-6 (MD = -0.24 ng/dL [95% CI, -0.36 to -0.13], I2 = 98.3%, p < 0.001), TNF-α (MD = -0.74 ng/dL [95% CI, -1.08 to -0.40], I2 = 98.8%, p < 0.001); and CRP (MD = -1.58 mg/L [95% CI, -2.22 to -0.94], I2 = 86.5%, p < 0.001). Notably, atorvastatin demonstrated the most significant reduction in IL-6 and TNF-α levels, while fluvastatin and rosuvastatin displayed the greatest impact on decreasing CRP and LDL-C levels, respectively. Stratification by a longer treatment duration of more than four months revealed that atorvastatin achieved the most significant reduction in IL-6 and TNF-α. In conclusion, statin therapy not only regulates the lipid profile but also reduces systemic inflammatory biomarkers. Prolonged administration of statins led to a more substantial reduction in IL-6 and TNF-α, with atorvastatin exhibiting the greatest effect in our analysis.